2019
DOI: 10.1080/09688080.2019.1571304
|View full text |Cite
|
Sign up to set email alerts
|

“Child marriage” in context: exploring local attitudes towards early marriage in rural Tanzania

Abstract: A global campaign to end "child marriage" has emerged over the last decade as part of growing international commitments to address gender inequities and improve female wellbeing. Campaigns typically assert that young brides have negligible autonomy in the marriage process and that marrying under 18 years has resolutely negative impacts on wellbeing. Yet, surprisingly few studies explore local attitudes towards marriage and its timing within contexts where early marriage is most common. As such our understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 31 publications
9
54
0
2
Order By: Relevance
“…The same is documented by the other researches and possible reasons behind early marriages were better adjustment in in-law family because younger girl can adopt and learn prevailing practices, an adult girl can be threat to honor of family, socio-cultural and religious practices, early marriage is a coping strategy to avoid evils and social pressure (Ferdous and Zeba 2019;Nasrullah, et al 2014, 3;Naveed and Butt 2015) This study demonstrates that childbearing is one of the important reasons behind early age pregnancies and even in certain cases a cause for child marriages as well. In this aspect this research study is aligned with the results of the Schaffnit, Urassa, and Lawson (2019) where both of the studies affirmed that soon after the marriage families expect a child from the newly married couple which causes pressure for early pregnancy. This is considered as a completion of family.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The same is documented by the other researches and possible reasons behind early marriages were better adjustment in in-law family because younger girl can adopt and learn prevailing practices, an adult girl can be threat to honor of family, socio-cultural and religious practices, early marriage is a coping strategy to avoid evils and social pressure (Ferdous and Zeba 2019;Nasrullah, et al 2014, 3;Naveed and Butt 2015) This study demonstrates that childbearing is one of the important reasons behind early age pregnancies and even in certain cases a cause for child marriages as well. In this aspect this research study is aligned with the results of the Schaffnit, Urassa, and Lawson (2019) where both of the studies affirmed that soon after the marriage families expect a child from the newly married couple which causes pressure for early pregnancy. This is considered as a completion of family.…”
Section: Discussionsupporting
confidence: 79%
“…In this context, a network of the 1000 civil society has been formed with the title "Girls Not Brides". Similarly, Sustainable Development Goals 2015 also showed commitment to eliminate harmful practices of early child marriages and forced marriage which is a universal reflection and commitment to address the issue of gender equality (Schaffnit, Urassa and Lawson 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our study is also relevant to current debates about the best definitions of childhood and adolescence. For example, following delayed transitions to adult social and economic independence in high-income countries, it has been recently proposed that the meaning of adolescence should be extended to refer to the ages of 10-24 years, as opposed to [10][11][12][13][14][15][16][17][18][19] years (33). These discussions should include a consideration of the potential for chosen terminology to lead to popular misunderstanding, and an acknowledgement of cultural and contextual variation in the timing of life transitions.…”
Section: Resultsmentioning
confidence: 99%
“…14). This stance contrasts a growing body of evidence that female adolescents are often active agents in the marriage process in some cultural contexts, and that early marriage does not always imply coercion or clear costs to wellbeing in the context of locally-available alternatives (15)(16)(17)(18)(19)(20). With such framing, the USA and other high-income populations are implicitly positioned as morally superior to those where child marriage is more common.…”
Section: Introductionmentioning
confidence: 92%
“…A recent study has shown that school failure is an important predictor of early marriages and pregnancy in addition to dropping out of school (26). In a recent international study investigating the motivations associated with early marriages, the fact that attending school is perceived by the immediate environment as a barrier to marriage, but the school failure or dropping out of school is a factor found to be related to the perception that especially girls are suitable for marriage for her 'reproductivity' independent of her age (17).…”
Section: Discussionmentioning
confidence: 99%